PENGARUH JUMLAH BELAHAN BONGGOL DAN UMUR BONGGOL TERHADAP PERTUMBUHAN TUNAS SECARA VEGETATIF PADA DUA VARIETAS TANAMAN PISANG - Marthadi, Marthadi; Radian, Radian; Wasian, Wasian (Agros Journal of Agriculture Science, 2024)
Increasing banana production by expanding land requires the availability of seeds in large and uniform quantities. One effort is to propagate by dividing the tubers. The banana varieties used have different characteristics in breeding. The number of splits will affect the size of the hump so that using a large hump will have more food reserves. The size of the weevil is closely related to the age of the weevil, the older the weevil, the larger the size of the weevil. This research aims to examine the role of variety, number of splits, age of the tuber and the interaction of the three on the vegetative growth of banana saplings. The study was conducted in Sanggau Regency, West Kalimantan, from October to December 2023. The study used a factorial randomized block design. The first factor is the treatment of varieties with 4 levels (chestnut and kepok pontia), the second factor is the treatment of the number of tuber sections with 4 levels (no split, 2, 4, and 8 splits), the third factor is the age of the tuber with 3 levels (1-2 months, 3-4 months, and 7-8 months). The tuber split treatment, and the age of the tuber independently played a role in influencing the time of shoot emergence, plant height, number of growing shoots, and stem diameter. Furthermore, the interaction between the number of weevil splits and the age of the weevil showed a real influence on the time when banana shoots emerged. 8-split weevils and 7-8-month-old weevils have better potential to produce banana seeds in large quantities.